A Study of Historical Values Toward Ecological Conservation in Muslim Communities - Atamimi, Abdul Basit; Sururi, Sofyan (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This research is motivated by issues related to ecological problems such as natural disasters, climate change, ecology, pollution and global warming today are the most important studies in the academic environment, environmental activists and state institutions. Through a historical approach, this qualitative study aims to highlight local wisdom-based environmental conservation patterns in the Sanghiang Site area, Majalengka Regency, West Java Province. Data were collected through documentation techniques, and data were analyzed using this analysis. The results of the study concluded that historically, efforts to preserve the local wisdom-based environment in the Sanghiang Site area cannot be separated from historical value, sacredness, and conservation. This conclusion can be seen in various aspects, including the dissemination of historical values in several places in the area. Then, the embedding of sacred titles in places that have historical value, and the installation of writings about the prohibition of activities that damage forests and trees. This research contributes to the importance of historical, cultural and religious values in ecological conservation.